Establishing State Raudhatul Athfal in West Kalimantan: A Critical Policy Analysis of Early Childhood Islamic Education - Hamzah, Nur; Ramadani, Laili (Institut Agama Islam Negeri Madura, 2026)
This study is grounded in the importance of providing quality early childhood education. Quality early childhood education has a positive impact, namely maximizing children’s growth and development and preparing them to enter the elementary school level. One of the efforts to provide quality education is the establishment of Raudhatul Athfal by the government through state Raudhatul Athfal. At the same time, in Indonesia, including West Kalimantan, to date there has not been a single state Raudhatul Athfal. Raudhatul Athfal managed by the state is intended to ensure that the quality of Islamic early childhood education is measurable, standardized, and equitable. This study aims to explore the expectations of teachers and students regarding the establishment of state Raudhatul Athfal, as well as to examine the responses and policies of the Ministry of Religious Affairs at the district/city level in West Kalimantan related to the establishment of state Raudhatul Athfal. This research employs a qualitative approach with a descriptive method. Data collection techniques include interviews, observation, and documentation. The key informants of the study consist of officials from the Ministry of Religious Affairs in West Kalimantan, Raudhatul Athfal teachers, and students of Early Childhood Islamic Education (Pendidikan Islam Anak Usia Dini/PIAUD). This study concludes that the establishment of state Raudhatul Athfal in West Kalimantan as an effort to implement quality Islamic early childhood education still has a long way to go due to the absence of policies from the Ministry of Religious Affairs in West Kalimantan regarding this issue, even though at the same time the encouragement and aspirations of teachers, alumni, students, and early childhood education activists for state Raudhatul Athfal are very strong.